An Improved Second Order Sliding Mode Twisting Algorithm for Finite-Time Trajectory Tracking of Intelligent Vehicle. (23rd December 2013) - Yang, Jie; Wang, Qinglin; Li, Yuan
Abstract : This paper proposes a kind of controller comprising Twisting algorithm and adaptive method for the trajectory tracking control of intelligent vehicle system with uncertainties. Firstly, by the adding the adaptive compensation controller, shortcomings of existing second order sliding mode Twisting algorithm are avoided. Second, based on the previosly improved method, we also add another kind of adaptive controller to make the controller parameters do not need to be selected. The intelligent vehicle system can achieve finite-time trajectory tracking, the upper bounds of the uncertainties do not need to be determined previously, and the controller parameters can be adjusted automatically according to the system state. The effectiveness and robustness of the improved algorithm are verified by theory and simulation results of the intelligent vehicle system.